Balik-Balara revitalizing the Balara Filters Park - Moises, Princess V. (College of Architecture, University of the Philippines Diliman, 2014)
The Balara Filters Park was known to be famous tourist spot of Quezon City during the 1950’s. It was where popular artists performed on stage and Filipino families used to have social gatherings. It was then neglected by most of the people when the owner, the Metropolitan Waterworks and Sewerage System (MWSS), focused more on refurbishing the water filtration services of Balara during the late 1950’s. The premise of this study is to revitalize the design of Balara Filter\s Park through promoting the civic interactions constructed in the past as a unifying factor of its cultural and industrial characteristics to make it once again the city’s alluring tourist spot. The concepts of Socio-Recreational Learning and Transcendence helps create a learning environment equipped structures that has a combination of past and present architectural styles of Balara that is experienced though recreational activities. From these concepts, proposed recreational spaces will be incorporated to the existing structures in the site. The integration of the past anf the present environment of Balara helps promote the importance of the social and civic interactions constructed in the past making it once again a recreational and cultural landmark of the city.